Policy alignment and trustworthy AI governance in higher education: A Conceptual Analysis of Malaysia’s Reform Agenda and ASEAN Governance Imperatives - Teoh, Kok Ban; Tan, Wee Ling (Journal of Interdisciplinary Studies in Education, 2026)
Artificial intelligence (AI) is increasingly reshaping higher education through learning analytics, assessment support, academic integrity monitoring, student services, and institutional decision-making. This conceptual paper examines how Malaysia’s higher education reform agenda can be aligned with ASEAN AI governance imperatives through the institutional role of universities. Using a qualitative policy-informed conceptual synthesis, the study identifies four governance gaps: human-centered values and operational oversight, institutional autonomy and accountability, AI adoption and institutional capacity, and regional principles and uneven implementation readiness. This paper proposes an integrated framework that links policy vision, institutional governance, educational practice, feedback-based learning, and ASEAN regional coordination. These findings suggest that universities should act as intermediary governance actors for the adoption of trustworthy AI.